2015
DOI: 10.1128/aac.00571-15
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Inhibition of Novel Bacterial Topoisomerase Inhibitors from Characterization of Resistant Mutants of Staphylococcus aureus

Abstract: The type II topoisomerases DNA gyrase and topoisomerase IV are clinically validated bacterial targets that catalyze the modulation of DNA topology that is vital to DNA replication, repair, and decatenation. Increasing resistance to fluoroquinolones, which trap the topoisomerase-DNA complex, has led to significant efforts in the discovery of novel inhibitors of these targets. AZ6142 is a member of the class of novel bacterial topoisomerase inhibitors (NBTIs) that utilizes a distinct mechanism to trap the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 41 publications
8
39
0
Order By: Relevance
“…Molecular characterization to determine the mechanism of the reduced susceptibility of these isolates was not performed. Previously, Lahiri et al showed for S. aureus that after initial bacterial killing in time-kill kinetics, a partial rebound of growth occurred when testing a representative NBTI compound (6). They also noted variations in the frequency of spontaneous resistance when testing S. aureus against representative NBTIs and found that the mutations that occurred were in the gyrase subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization to determine the mechanism of the reduced susceptibility of these isolates was not performed. Previously, Lahiri et al showed for S. aureus that after initial bacterial killing in time-kill kinetics, a partial rebound of growth occurred when testing a representative NBTI compound (6). They also noted variations in the frequency of spontaneous resistance when testing S. aureus against representative NBTIs and found that the mutations that occurred were in the gyrase subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Gepotidacin and other mechanistically related (but structurally different) NBTIs have a mode of action which differs from fluoroquinolones in that they bind to the DNA-protein complex at a location that is away from the cleavage site and do not form a cleavage complex (12,13). Since gepotidacin and NBTIs bind at a different location than fluoroquinolones, they have demonstrated in vitro activity against strains resistant to other antibacterial classes, including fluoroquinolones (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…New approaches to combat antibiotic resistance include targeting the synthesis of aminoacyl‐tRNA synthetases (aaRS) and charging of tRNA, DNA replication, RNA transcription, the action of topoisomerases and riboswitches that carry out essential bacterial cell functions . Riboswitches are suitable targets for intervention as they have highly selected metabolite receptors located within the 5′‐untranslated region (5′UTR) of messenger RNAs (mRNA) controlling transcription or translation and are validated targets for intervention .…”
Section: Introductionmentioning
confidence: 99%
“…New approaches to combat antibiotic resistance include targeting the synthesis of aminoacyl-tRNA synthetases (aaRS) and chargingo ft RNA, DNA replication,R NA transcription,t he action of topoisomerases and riboswitches that carry out essentialb acterial cell functions. [10][11][12][13][14][15] Riboswitches are suitable targets for intervention as they have highly selected metabolite receptors located within the 5'-untranslated region (5'UTR) of messenger RNAs (mRNA) controlling transcription or translation [16] and are validated targets for intervention. [17,18] For example,a na nalogue of an atural metabolite could control expression of as ingle essential gene by outcompeting the metabolite or alteringt he RNA conformation and disrupting normalexpression patterns.…”
Section: Introductionmentioning
confidence: 99%